Analysis of the Influence of Ecology on Human Resources Management in the Healthcare System - BAIGIREYEVA, Zhanar; BEISENGALIYEV, Berik; KICHA, Dmitry; NIYAZBEKOVA, Shakizada; MAISIGOVA, Leila (Journal of Environmental Management and Tourism; Vol 12 No 7 (2021): JEMT Volume XII, Issue 7(55), Winter 2021DO - 10.14505/jemt.v12.7(55).23, 2021)
One of the priorities of the institutional and structural reforms implemented by Kazakhstan during the years of its independence is the formation of systemic conditions for the development and growth of the country's human capital. The issue of human capital development has always been in the focus of both conceptual documents defining the strategy for the development of the state and society, and real actions taken by the country's political leadership. Coming to the forefront of human capital is one of the modern global trends. Human capital is the main economic resource of the XXI century, increasing the country's GDP, which has become the main productive and social factor in the development of the economy of the Republic of Kazakhstan. The purpose of the study of the impact of ecology on human resource management is to analyze the formation and development of human resources by highly qualified specialists and employees capable of meeting the tasks and activities aimed at further improving the health care system in the Republic of Kazakhstan to ensure a high level of quality in the provision of medical services.